Volume 1: Aircraft Engine; Marine; Turbomachinery; Microturbines and Small Turbomachinery 2000
DOI: 10.1115/2000-gt-0432
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Unsteady Rotor Flow Field in a Single HP Turbine Stage

Abstract: Within a European project a high-pressure turbine stage was investigated at DLR, Göttingen. The investigations consisted primarily of experiments carried out in the windtunnel for Rotating Cascades (RGG), but some numerical work was also performed. Detailed measurements were carried out at mid section of a turbine rotor using a Laser-2-Focus device which served as a velocimeter measuring 2D-velocity vectors and turbulence quantities and as a tool to determine the concentration of coolant ejected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…It is noteworthy that despite a relatively large number of both numerical and experimental studies on W/R interaction which were recently published, finding appropriate data in which the wake development analysis goes as deep as to the vortex structure of the wake was extremely difficult. The most comprehensive and most valuable analysis from the point of view of the present validation was published by Kost et al [33]. When comparing the experimental and VDT curves in successive diagrams we can notice high similarity of their patterns, especially at points located close to the pressure side of the rotor blade.…”
Section: Numerical and Experimental Validationmentioning
confidence: 67%
“…It is noteworthy that despite a relatively large number of both numerical and experimental studies on W/R interaction which were recently published, finding appropriate data in which the wake development analysis goes as deep as to the vortex structure of the wake was extremely difficult. The most comprehensive and most valuable analysis from the point of view of the present validation was published by Kost et al [33]. When comparing the experimental and VDT curves in successive diagrams we can notice high similarity of their patterns, especially at points located close to the pressure side of the rotor blade.…”
Section: Numerical and Experimental Validationmentioning
confidence: 67%
“…Further behaviour of the stator and rotor wakes can be observed in Fig. 4 being a compilation of the results presented in [23][24][25][26][27]. All wakes leave the rotor moving, generally, in the direction of the main flow velocity w 2 .…”
Section: Wake Deformation and Physical Nature Of Clockingmentioning
confidence: 83%
“…Some initial attempts to take into account vortex dynamics when analysing the stator wake motion through the rotor cascade have been published. A most detailed study was done by Kost et al [23], Tiedemann and Kost [24] and Hummel [25], who examined experimentally and numerically unsteady flow fields generated by stator wakes in rotor passages of a full size aero-engine high-pressure turbine stage having 43 stator blades and 64 rotor blades. Visual studies of the flow inside the rotor passages performed by Kost et al with the aid of coolant injected to the flow at the vicinity of stator blade trailing edges have revealed that on its way through the rotor passage the stator wake forms two separate areas of different-sign vorticity which move one after the other through the passage, thus creating the earlier mentioned negative jet between the blade walls, clearly observed on the numerically calculated distributions of velocity vectors.…”
Section: Wake Deformation and Physical Nature Of Clockingmentioning
confidence: 99%
“…However, FlowER was used by the author in the past for studying the 2D flow structure in a HP turbine rotor passage [9]. In that study the pattern of stator wake development in the rotor passage was analysed by comparing the results obtained from FlowER with those given by the vortex dynamics theory, which, in turn, had been validated using the results recorded by Kost on a model turbine [10]. This study is a continuation and 3D extension of that presented in 2002.…”
Section: Fig 1 Turbine Stage Geometrymentioning
confidence: 99%